2017
DOI: 10.1161/jaha.116.005135
|View full text |Cite
|
Sign up to set email alerts
|

Switch From Fetal to Adult SCN5A Isoform in Human Induced Pluripotent Stem Cell–Derived Cardiomyocytes Unmasks the Cellular Phenotype of a Conduction Disease–Causing Mutation

Abstract: BackgroundHuman induced pluripotent stem cell–derived cardiomyocytes (hiPSC‐CMs) can recapitulate features of ion channel mutations causing inherited rhythm disease. However, the lack of maturity of these cells is considered a significant limitation of the model. Prolonged culture of hiPSC‐CMs promotes maturation of these cells. We studied the electrophysiological effects of the I230T mutation in the sodium channel gene SCN5A in hiPSC‐CMs generated from a homozygous (I230Thomo) and a heterozygous (I230Thet) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 43 publications
5
37
1
1
Order By: Relevance
“…Again, recording conditions may play a role [ 4 ], but additional factors such as the employed hiPSC-CMs line, differentiation and dissociation protocols, and the time interval between differentiation and AP recording may also contribute substantially to the apparent differences. Nevertheless, the APD values obtained in the present study are close to the values that we previously observed in our laboratory for control hESC-CMs and hiPSC-CMs [ 5 , 21 , 22 , 26 , 27 , 36 , 37 , 38 , 39 , 40 ]. Preliminary follow-up experiments demonstrate the virtual lack of a carbachol-activated current in our control hiPSC-CMs [ 41 ], which further demonstrates the ventricular nature of these cells, but opposes our speculation regarding the likely presence of “natural” atrial-like hiPSC-CMs in the CTRL group of our present study.…”
Section: Discussionsupporting
confidence: 91%
“…Again, recording conditions may play a role [ 4 ], but additional factors such as the employed hiPSC-CMs line, differentiation and dissociation protocols, and the time interval between differentiation and AP recording may also contribute substantially to the apparent differences. Nevertheless, the APD values obtained in the present study are close to the values that we previously observed in our laboratory for control hESC-CMs and hiPSC-CMs [ 5 , 21 , 22 , 26 , 27 , 36 , 37 , 38 , 39 , 40 ]. Preliminary follow-up experiments demonstrate the virtual lack of a carbachol-activated current in our control hiPSC-CMs [ 41 ], which further demonstrates the ventricular nature of these cells, but opposes our speculation regarding the likely presence of “natural” atrial-like hiPSC-CMs in the CTRL group of our present study.…”
Section: Discussionsupporting
confidence: 91%
“…In hiPSC-CMs, T-tubules are absent and SR is underdeveloped with low expression of SERCA and other key proteins. As a result, hiPSC-CMs rely on L-type channels for the increase of Ca 2+ and ECC is slow (Pesl et al, 2017;Veerman et al, 2017).…”
Section: Calcium Handlingmentioning
confidence: 99%
“…Furthermore, their current density was found to increase from day 30 to 80 of the differentiation process. Consequently, temporal changes of these properties determine different ionic contribution to the cardiac AP (I Na , I CaL , I K1 ), leading to heterogeneous AP profiles and parameters (diastolic membrane potential, E diast ; AP amplitude, APA; AP duration, APD) [91][92][93].…”
Section: Functional Properties Of Hipsc-cms: Overview and Limitationsmentioning
confidence: 99%